Migrants, asylum seekers and refugees in Greece in the midst of the COVID-19 pandemic - Fouskas, Theodoros (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
COVID-19 cases detected in accommodation centers in mainland Greece, while thousands of asylum seekers, refugees, and migrants are living under unsafe and degrading conditions at the camps on the Aegean islands and others in the mainland. They live mostly in overcrowded Reception and Identification Centers (RICs) and accommodation centers under deplorable conditions, the lack of proper shelter, the extremely unhygienic living conditions. Migrants, asylum seekers and refugees living in the RICs faced multiple challenges and vulnerabilities that must be considered when responding to the COVID-19 pandemic.